Semantic Mapping Strategy dan Progres Pemahaman Qawaid Bahasa Arab di Pondok Pesantren Mamba’ul Falah Kudus - Nafisah, Jauharotun; Astina, Chairani; Aulia Rahman, Rifqi (Al-Jawhar : Journal of Arabic Language, 2023)
This study aims to investigate the implementation progress of the semantic map strategy in qawaid learning at the Manbaul Falah Kudus Islamic boarding school. It also aims to examine the improvement in qawaid learning outcomes at the school after implementing the strategy, as well as the differences in qawaid learning outcomes before and after using the strategy. The research adopts a quantitative approach and falls under the category of field research. It was conducted at the Manbaul Falah Islamic Boarding School in Kudus, using an experimental research design with a quasi-experimental design that includes both an experimental class and a control class. Data collection methods employed in this study include observations, interviews, documentation, and tests. The findings of the research indicate the following: 1) There is a significant increase in the qawaid learning outcomes for the experimental class, with a gain value of 0.709 in the high category. 2) There is a significant difference in the qawaid learning outcomes before and after implementing the Semantic Map Strategy (SMS), as evidenced by the t-test calculations. The obtained t-value is 3.64, while the t-table value at a significance level of 5% and degrees of freedom (df) = (15+10)-2 = 23 is 2.069. Additionally, at a significance level of 1%, the t-table value is 2.807. The results indicate that the t-value is greater than the t-table value. Thus, it can be concluded that there are significant differences in the qawaid learning outcomes between classes that utilize the Semantic Map Strategy (SMS) and those that do not.